Modeling and simulation of three phases cascaded H-bridge grid-tied PV inverter - Swetapadma Panigrahi; Amarnath Thakur (Institute of Advanced Engineering and Science, 2019)
In this paper a control scheme for three phase seven level cascaded H-bridge inverter for grid tied PV system is presented. As power generation from PV depends on varing environmental conditions, for extractraction of maximum power from PV array, fuzzy MPPT controller is incorporated with each PV array. It gives fast and accurate response. To maintain the grid current sinusoidal under varying conditions, a digital PI controller scheme is adopted. A MATLAB/Simulink model is developed for this purpose and results are presented. At last THD analysis is carried out in order to validate the performance of the overall system. As discussed, with this control strategy the balanced grid current is obtained keeping THD values with in the specified range of IEEE-519 standard.